Imaging from cells to animals in vivo - Barroso, Margarida; Intes, Xavier (Boca Raton : CRC Press, 2020)
"Imaging from Cells to Animals In Vivo offers an overview of optical imaging techniques developed over the last two decades to investigate biological processes in live cells and tissues. It comprehensively covers the main imaging approaches used, as well as the application of those techniques to biological investigations in preclinical models. Among the areas covered are cell metabolism, receptor-ligand interactions, membrane trafficking, cell signaling, cell migration, cell adhesion, cytoskeleton and other processes using various molecular optical imaging techniques in living organisms, such as mice and zebrafish. Features Brings together biology and advanced optical imaging techniques to provide an overview of progress and modern methods from microscopy to whole body imaging Fills the need for a comprehensive view of application-driven development and use of new tools to ask new biological questions in the context of a living system. Includes basic chapters on key methods and instrumentation, from fluorescence microscopy and imaging to endoscopy, optical coherence tomography, and super-resolution imaging. Discusses approaches at different length scales and biomedical applications to the study of single cell, whole organ, and whole organism behavior. Addresses the impact on discovery, such as cellular function as implicated in human disease, and translational medicine, for example in cancer diagnosis"--
OCLC-licensed vendor bibliographic record.
Keywords: Imaging systems in biology; Imaging systems in medicine; Diagnostic imaging -- Digital techniques; SCIENCE / Research & Methodology; SCIENCE / Physics